Exogenous spillover coefficients in economics: Case of reciprocal pollution - Raimund Krumm (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
Indicators based on spillover coefficients contribute to the characterization of reciprocal externality fields. Such indicators can describe both quantity and structure aspects of diffiision schemes. In this paper the significance of spillover coefficients and corresponding indicators for bilateral externality coordination is demonstrated. Among other things, their relevance in instrumental designing is analysed. Finally "extended" spillover coefficients are derived, including damage aspects of external effects in addition to diffiision phenonema.
Keywords: 330; external effects; externality indicators; pollutant diffiision; damage costs; policy coordination; emission taxes; air pollution; water pollution; Externer Effekt; Spillover-Effekt; Wirtschaftsindikator; Umweltökonomik; Theorie